Cursed: a social portrait of the Kielce pogrom - Tokarska-Bakir, Joanna (Cornell University Press, 2018)
"Based on previously unexamined archival records and oral testimonies, the book details the 1946 Kielce pogrom, in which many dozens of Jews were killed or wounded. Shocked Polish Jews, most of whom had survived ghettos and death camps or exile in the Soviet Union, fled to the West, bringing nearly to an end a thousand years of Jewish life in Poland"-